PERHITUNGAN STRUKTUR BENDUNG MEJANG DESA MIAU BARU KABUPATEN KUTAI TIMUR KALIMANTAN TIMUR - ISNAINI RACHMI, THIA (KURVA S JURNAL MAHASISWA, 2016)
Structure estimation step of weir starts by estimation the value of flood design in 25 years return period flood design is used to design the dimention of weir. weir dimention is used to calculate all kind of pressure which is work in this weir. Beside that, structure estimation of weir is also used to find the value of base reaction, maximum pressure, minimum pressure and moment ultimate by using SAP 2000 software which is calculated in three kind of water level conditions. They are Normal Water Level, Maximum Flood Water level, and Empty water level. And then, to find the weir’s safety factor in sliding, overtunig and piping, we anylized the stability of weir. The result of weir’s structure estimation are designe of water discharge 334,243 m³/second for flood design in 25 years return period. Hydrolic design used 334,243 m³/second for flood design in 25 years return period and the result are fixed weir type with round top point and Vlughter type for energy absorbers basin, height of weir is about 3 m, effective width of weir is about 15,69 m, radius of weir’s top point is about 0,70 m, length of  energy absorbers basin is about 10,54 m, length of downsteram floor is about 15.00 m and length of creep is about 45,75 m. Maximum stress is occured in maximum flood design condition, in SAP 2000 software, it’s called S11 stress, the maximum S11 stress is about 4222596,47 Kg/m2, minimum S11 stress is about -8062517,95 Kg/m2 and maximum base reaction is about 291759,31 kg. All safety analyzing is secure and compatible with safety factor. Base on the result of weir structure estimation above can be concluded that the dimention of weir from flood design in 25 years return period is capable to resist all pressures that consist in it and overall the weir condition is secure.